PS 13-15 CARVEDILOL ATTENUATES MECHANICAL STRETCHED MYOCARDIAL MITOCHONDRIA DYSFUNCTION BY PREVENTING TELOMERE-P53 PATHWAY. (September 2016) - Okada, Motoi; Kashiwagi, Yuta; Fujita, Satoshi; Hasebe, Naoyuki
Abstract : Objective: Cardiac hypertrophy increases with aging. It is known to cause the heart failure after the long-term pressure load. It has been reported that short telomere length and mitochondrial dysfunction were increasing with aging or aging-related diseases. Carvedilol is known as a convalescence improvement medicine for heart failure, but the mechanism has not been investigated in detail. P53 plays a role in regulating mitochondrial function through peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1a) repression. In this study, we investigated the effects of beta blocker carvedilol on telomere dependent apoptotic signal in mechanical stretched myocardium. Design and Method: We used H9C2 rat cardiomyocytes incubated with mechanical stretch chamber. Cells were subjected to 20 % cyclic uniaxial stretch for 72 h at a frequency of 1 Hz. We studied qPCR for the influence of various concentration of carvedilol (Carv). We estimated telomere length by Quantitative fluorescent in situ hybridization (Q-FISH) analysis. We also evaluated mitochondrial function using Mito tracker and cytochrome C activity. TUNEL assay was performed for evaluation of apoptosis. Results: Stretched cells showed reduced expression of tert, bcl-2, cleaved caspase-3, pgc-1a and increased expression of p53. Q-FISH analysis showed short telomere length. Whereas H9C2 cells treated with 0.1, 1, 10uM of Carv showed increased telomerase activity and reduced expression of p53 and telomere re-lengthening in a concentration dependent manner. Mitochondrial function which was measured by Mito tracker and cytochrome C activity assay also improved in Carv. Carv markedly reduced expression of TUNEL positive cell in the stretched cells. Conclusions: These results demonstrated that carvedilol was able to protect against myocardial mitochondria dysfunction and apoptosis by mechanical stretch stimulation. It suggested that carvedilol has a potential for the treatment of aging-related disease through the telomere-p53-PGC pathway.